Tourism in the global development strategy of Macedonia: Economic perspectives - Biljana Petrevska (UTMS Journal of Economics, 2011)
This case study makes an attempt to identify the adequate position of tourism within the global development strategy of Macedonia. The paper discusses two, extremely opposite attitudes. The first, argues that necessary preconditions must be established in order tourism to have intensive development, thus clearly stating in the development strategy the priority orientation of tourism industry. The second underlines the fake image of tourism and its economic contributions. The paper brings out results of a comprehensive analysis of direct economic tourism effects, hence making clarification whether tourism sector has significant contribution within the entire economy, its influence on the employment, as well as its effects on the balance of payments.
Keywords: 330; tourism; economic effects; tourism strategy; development